Acute effects of different exercise forms on executive function and the mechanism of cerebral hemodynamics in hospitalized T2DM patients: a within-subject study - Wang, Haolin; Tang, Wei; Zhao, Yanan (Frontiers in Public Health, 2023)
Objective: This study aimed to investigate the acute effects of aerobic exercise (AE), resistance exercise (RE) and integrated concurrent exercise (ICE; i.e., AE plus RE) on executive function among the hospitalized T2DM inpatients, and the mechanism of cerebral hemodynamics. Methods: A within-subject design was applied in 30 hospitalized patients with T2DM aged between 45 and 70 yrs in Jiangsu geriatric hospital, China. Participants were asked to complete AE, resistance and ICE on three days with 48 h interval. Three executive function (EF) tests, namely Stroop, More odd shifting and 2-back tests were applied at baselineand after each exercise. The functional near-infrared spectroscopy brain function imaging system was used to collect cerebral hemodynamic data. The one-way repeated measurement ANOVA was used to explore training effects on each test indicator. Results: Compared with the baseline data, the EF indicators have been improved after both ICE and RE (p＜0.05). Compared with AE, ICE and RE groups have demonstrated significant improvements in inhibition (ICE: MD = 162.91ms; RE: MD = 106.68ms) and conversion function (ICE: MD = 111.78ms; RE: MD = 86.95ms). Based on the cerebral hemodynamic data, the concentration of Oxyhemoglobin (HbO2) in the brain regions related to executive function increased after three kinds of exercise, and the EF improvements after the ICE showed synchronous activation of blood flow in dorsolateral prefrontal cortex (DLPFC) and frontal polar, and the improvement of inhibitory function after RE displayed synchronous activation of DLPFC. The HbO2 concentration in the Pars triangularis Broca's area increased significantly after AE, but the executive function did not improve significantly. Conclusion: The ICE is preferred in the improvements of executive function in T2DM patients; while RE is preferred for the improvements of inhibitory function. Moreover, a synergistic mechanism exists between cognitive function and blood flow activation in specific brain regions.